Macrofauna Diversity Associated with Mangrove Roots in West Lombok Regency - Wahyu Bintang Ilahi; Muhlis Muhlis; Abdul Syukur (Jurnal Biologi Tropis, 2023)
Mangrove is an ecosystem that has a wealth of macrofauna, which includes plant species and biota associated therein, gastropods and bivalves associated with mangroves as living habitat, shelter, spawning and food supply. The purpose of this study was to determine the diversity of macrofauna associated with mangrove species. This research is a quantitative descriptive research with a survey method. The results showed that the diversity of gastropods and bivalves on the gastropod Cemara beach was 2.05. Bivalvia 1.22. Meanwhile in Bagek Kembar. Gastropods 1.73 and bivalvia 1.32 have relatively low diversity. The results of the analysis using the contingency table at the study site were 8 pairs from the Gastropod class and 4 pairs from the Bivalvia class, these pairs tended to associate at the 5% test level. The macrofauna and mangrove species pairs obtained had a positive association of 6 pairs, namely (Telescopium -Avicennia lanata, Terebralia sulcata -Avicennia lanata, Cerithideacingulata-Rhizophora mucronata, Cerithidea cingulata-Avicennia marina, Cerithideacingulata-Sonneratia caseolaris, Batillaria zonalis -Rhizophora stylosa) whereas in class bivalves there are 4 pairs (Anadara antiquata -Avicennia lanata, Anadara antiquata -Ceriops decandra, Gafrarium pectinatum -Avicennia lanata, Lutraria lutraria-Rhizophora mucronata). This pair of macrofauna with mangrove species shows a close relationship between the two. For future mangrove planting, it can be used as a benchmark by looking at macrofauna and mangrove pairs that are positively associated.